STUDI APLIKASI EFEK FOTOKATALIS ZnO:Ag DIKOMBINASI OZON PADA PROSES PENCUCIAN CABAI - Sutanto, Heri; Arifin, Zaenal; Wibowo, Singgih; Hidayanto, Eko (BERKALA FISIKA, 2015)
In this study, we have done evaluation of photocatalyst and ozone effect on chilies. The photocatalyst thin film was made by Ag doped zinc oxide (ZnO). The film was evaluated by X-ray diffractometer (XRD), Scanning Electron Microscopy (SEM) and UV-Vis for crystall stucture, morphology and optical band gap analysis. XRD result showed that the film has hexagonal wurtzite structure with crystallite size about 19.93 nm. From SEM result, morphology of film was not homogen and there were a lot of pores. From UV-Vis measurement, we could calculate the optical band gap of film about 3.081 eV.Â The chilies that used is hot peppers. They were washed by water from ZnO:Ag photocatalyst and ozone treatment. Time for water treatment was adjusted for 0, 15, 30 and 45 min. We have done monitoring on loss of mass of the chilies. The result showed thatÂ 15 min sample showed better result than other sample. In this sample, the chilies had smallest change of loss mass in 13 day observation. Keywords : Photocatalyst, ozone, chilies.